Ranking the Personal Excellence Training Needs of Undergraduate Tourism Students - Min, Jennifer; Tang, Hui-Wen Vivian; Chen, Chun An (Journal of Tourism Management Research, 2016)
Increased attention has been devoted to the issue of pursuit of personal excellence in the higher education in Taiwan in order to enhance the teaching quality and increase students’ competition. While the government has devoted considerable efforts and funding to education institutions through different academic excellence plans, there has been relatively little discussion of pursuit of excellence among student population, nor have there been any curriculum or training programs designed for students to improve their personal excellence. Thus, the present study aims to fill the research gap by designing a training program for the personal excellence of undergraduate tourism students in Taiwan. Grey Relational Analysis (GRA), a multi-criteria decision analysis method, is conducted to prioritize personal excellence training needs for tourism students. The training programs are then developed with a focus on enhancing weak areas of personal excellence competence for tourism students. It is hoped that the results can give students an advantage in entering and staying in their chosen industry, leading to success in both their professional and personal lives.